Pengembangan Aplikasi Serah Terima Dokumen Order dengan Metode User Centered Design - Pamuji, Gede Maharta; Mogi, I Komang Ari (Jurnal Nasional Teknologi Informasi dan Aplikasnya, 2022)
The process of handing over the order contract document is a process that is usually carried out between the seller and the expedition as a contract in the delivery of goods. PT Enseval Putera Megatrading Tbk Denpasar is one of the companies that carried out this handover process. However, in the process, difficulties are often encountered, so a web-based order handover application was built to smooth out the process of handing over order contract documents. This study discusses how to develop an application that involves the user directly. The method used in this research is User Centered Design (UCD), where the application development process always involves the users, starting from planning to testing, where the usability aspect of the application will be tested.